Types Of Translation Shifts In Relative Clauses Found In The Novel Entitled “The Wonderful Wizard Of OZ” - I Gede Nika Wirawan (Denpasar Institute, 2023)
This study focuses on analysis of types of translation shifts in English relative clauses found in the novel entitled “The Wonderful Wizard of Oz”. The study aims to analyze the types of translation shifts in relative clauses found in the novel entitled “The Wonderful Wizard of Oz”. In analyzing data, the theory of relative clauses by Quirk (1985), Sneddon (1996) and the theory of translation shift proposed by Catford (1965) were used. In analyzing the types of translation shifts found in relative clauses, this study applied qualitative research method. The researcher got the data of relative clauses and its translation by reading and collecting data in the novel entitled “The Wonderful Wizard of Oz” to find out the story and observe the possibility of the data source taken from the novel. In the method and technique of collecting the data, the data source the novel entitled “The Wonderful Wizard of Oz” was read to find out types of translation shifts found in the novel entitled “The Wonderful Wizard of Oz”. The analysis of relative clauses found that type of translation shifts found in English relative clauses in the novel entitled “The Wonderful Wizard of Oz” were unit shifts translation and structure shifts. The strength in the analysis of this study is placed on the translation shifts analysis found in the novel entitled “The Wonderful Wizard of Oz”